Cooperative effects in the detection of a nitroaliphatic liquid explosive and na explosive taggant in the vapor phase by calix[4]arene-based carbazole-containing conjugated polymers - D. Barata, Patrícia (2014)
Two fluorescent molecular receptor based conjugated polymers were used in the detection of a nitroaliphatic liquid explosive (nitromethane) and an explosive taggant (2,3-dimethyl-2,3-dinitrobutane) in the vapor phase. Results have shown that thin films of both polymers display remarkably high sensitivity and selectivity toward these analytes. Very fast, reproducible, and reversible responses were found. The unique behavior of these supramolecular host systems is ascribed to cooperativity effects developed between the calix[4] arene hosts and the phenylene ethynylene-carbazolylene main chains. The calix[4]-arene hosts create a plethora of host-guest binding sites along the polymer backbone, either in their bowl-shaped cavities or between the outer walls of the cavity, to direct guests to the area of the transduction centers (main chain) at which favorable photoinduced electron transfer to the guest molecules occurs and leads to the observed fluorescence quenching. The high tridimensional porous nature of the polymers imparted by the bis-calixarene moieties concomitantly allows fast diffusion of guest molecules into the polymer thin films.